2020
DOI: 10.3390/ijms21165685
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast Multinucleation: Review of Current Literature

Abstract: Multinucleation is a hallmark of osteoclast maturation. The unique and dynamic multinucleation process not only increases cell size but causes functional alterations through reconstruction of the cytoskeleton, creating the actin ring and ruffled border that enable bone resorption. Our understanding of the molecular mechanisms underlying osteoclast multinucleation has advanced considerably in this century, especially since the identification of DC-STAMP and OC-STAMP as “master fusogens”. Regarding the molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 208 publications
(299 reference statements)
3
73
2
2
Order By: Relevance
“…DCSTAMP and OCSTAMP proteins represent an interesting group of proteins to study in the context of cell-cell fusion, since they have been shown to play a role in osteoclast and foreign body giant cell (FBGC) fusion 1315 . They belong to the class of DC-STAMP-like domain-containing proteins, and are multi-pass transmembrane proteins with an intracellular C-terminus containing a non-canonical RING finger domain 13,16,17 . DCSTAMP was shown to localize to the plasma membrane and endoplasmic reticulum (ER) membrane in dendritic cells and osteoclasts 1619 .…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…DCSTAMP and OCSTAMP proteins represent an interesting group of proteins to study in the context of cell-cell fusion, since they have been shown to play a role in osteoclast and foreign body giant cell (FBGC) fusion 1315 . They belong to the class of DC-STAMP-like domain-containing proteins, and are multi-pass transmembrane proteins with an intracellular C-terminus containing a non-canonical RING finger domain 13,16,17 . DCSTAMP was shown to localize to the plasma membrane and endoplasmic reticulum (ER) membrane in dendritic cells and osteoclasts 1619 .…”
Section: Main Textmentioning
confidence: 99%
“…They belong to the class of DC-STAMP-like domain-containing proteins, and are multi-pass transmembrane proteins with an intracellular C-terminus containing a non-canonical RING finger domain 13,16,17 . DCSTAMP was shown to localize to the plasma membrane and endoplasmic reticulum (ER) membrane in dendritic cells and osteoclasts 1619 . These cell types in Dcstamp KO mice show no apparent defect in differentiation into the osteoclast lineage and cytoskeletal structure, yet osteoclasts and FBGCs are unable to fuse to form terminally differentiated multinucleated cells 14 .…”
Section: Main Textmentioning
confidence: 99%
“…OCLs develop from haematopoietic stem cells through a series of morphological and functional transformations that lead to the establishment of multinucleated polarized cells (Kodama and Kaito, 2020). These are able to migrate toward bone, adhere to it, and resorb the tissue beneath in a controlled manner (Bruzzaniti and Baron, 2006;Teitelbaum, 2007).…”
Section: The Osteoclast Cellmentioning
confidence: 99%
“…The impaired formation F-acting ring also con rmed the ndings above. Moreover, we discovered that CIM downregulated expression of speci c genes in osteoclast, including those involved in regulation of downstream genes expression (Nfatc1, c-Fos and Traf6) 31 , bone resorption function (Cathepsin K and Acp5) 32 , calcium homeostasis (Calcr) 33 , and cell fusion of precursors (Dc-stamp) 34 .…”
Section: Discussionmentioning
confidence: 99%